Konsep Pembentukan Personal Branding Peter Montoya Pada Akun Instagram @satriviavijie - Adevy, Vanie; Naila, Filzani (Jurnal Mahardika Adiwidia, 2024)
This research aims to understand the concept of forming Peter Montoya's personal branding on the Instagram account @satriavijie. The approach used is descriptive qualitative. Montoya's eight personal branding concepts consist of, Specialization which is concentrated on strengths, skills or achievements. Leadership, providing clear direction to meet their needs. Personality is based on the personality that is. Differences are shown in a different way than others. The appearance of being someone who seems to need to promote himself, using every opportunity he encounters. Unity must be in line with moral ethics and attitudes. Firmness, a person must remain steadfast to the initial personal brand that has been formed and a good name lasts longer if it is perceived positively. The result is that Satria Vijie formed Personal Branding on Instagram by having a strong relationship with followers, providing motivation on his Instagram social media, sharing information about Skateboarding, carrying out positive activities starting from creating a social movement to educating children who are at LPKA. Satria Vijie built a Skatepark for Skaters thereby creating a positive perception in the minds of the public.